2024
DOI: 10.1186/s12944-024-02045-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of triglyceride glucose-body mass index and hemoglobin glycation index with heart failure prevalence in hypertensive populations: a study across different glucose metabolism status

Rupeng Wang,
Ce Chen,
Guiyu Xu
et al.

Abstract: Background The Triglyceride glucose-body mass index (TyG-BMI) and hemoglobin glycation index (HGI) are well-established surrogate markers for insulin resistance. Nevertheless, the extent to which these markers offer additive predictive value for heart failure (HF) prevalence in hypertensive populations, and their predictive utility across various diabetic statuses, remains to be clarified. Consequently, this study aimed to explore the independent and synergistic effects of TyG-BMI and HGI on HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Some studies have found a positive link between HGI and hypertension, but results vary ( 12 ). In a cross-sectional study, high HGI independently associated with risk of hypertension ( 13 ).In another cross-sectional study, HGI was also found to be predictive of the development of heart failure in a hypertensive population ( 14 ). Research on how HGI affects CVD and all-cause mortality in hypertensive patients is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found a positive link between HGI and hypertension, but results vary ( 12 ). In a cross-sectional study, high HGI independently associated with risk of hypertension ( 13 ).In another cross-sectional study, HGI was also found to be predictive of the development of heart failure in a hypertensive population ( 14 ). Research on how HGI affects CVD and all-cause mortality in hypertensive patients is limited.…”
Section: Introductionmentioning
confidence: 99%